Pengaruh Problem Based Learning Terhadap Peningkatan Kemampuan Berpikir Kreatif Matematika Siswa Kelas VIII SMPN 6 Kupang Tengah SATAP Pada Materi Sistem Persamaan Linear Dua Variabel - Primusandy Leokoy (Universitas Nusa Cendana, 2022)
The aim of this research is to find out if there is an effect of problem based learning on the improvement of mathematical creative thinking ability of eighth grade students of SMPN 6 Kupang Tengah SATAP on the material of a two-variable linear equation system. This type of research is a pre-experimental research with one group pretest-posttest research design. This research was conducted at SMPN 6 Kupang Tengah SATAP on grade VIII students. The research instrument was in the form of test at the beginning of learning (pre-test) and test after the end of learning activities (post-test). Before using the instrument, validity and reliability tests. Furthermore, data analysis was carried out using normalized N-Gain calculations and through the stages of normality test and hypothesis test. The results showed that there was an increase in the average pre-test and post-test results after giving an experiment with the score 0.34 and the increase also occurred in every indicator of creative thinking ability which is detailed as follows: the score of originality 0.41, fluency 0.4, flexibility 0.21 and elaboration 0.38. Overall, the increase for each indicator of creative thinking is in the medium category, which is 0.35.